Utilization of Horticultural Waste as a Jumputan Batik Dye at MSMEs Wong Kito Gallery - Sari, Ira Maya; Ulpa, Maya; Handayani, Afrida Rahma; Puspitahati, Puspitahati (Program Pascasarjana Universitas Sriwijaya, 2024)
Abstract: The purpose of this research is to find out and analyze the use of horticultural waste as dyes in the manufacture of natural batik in MSMEs Galeri Wong Kito Palembang city. The research was conducted from September 2023 to February 2024 at MSMEs at the Wong Kito Gallery, Palembang City. The methods in this study were 1) Observed directly to the MSMEs of the Wong Kito Gallery to see the batik production process and the use of horticultural waste dyes, 2) Interviews with batik owners and artisans at Wong Kito Gallery to get information about dyeing techniques,3) Literature Study. Data Analysis was carried out descriptively data in the form of tables, graphs, and qualitative analysis to conclude the effect of natural coloring on the quality of batik based on the results of interviews and observations. The result of this paper were 1) The Pesona Sriwijaya Group is committed to sustainability by strengthening the community and being an example in CSR programs that are not only socially and environmentally responsible, but also provide concrete benefits for people's daily lives. The synergy and collaboration between five groups (Keramasan Crafter, Bukit Crafter, Aksara Group, Indonesian Disabled Women's Association (HWDI), Hijrah), all of which were fostered by Wong Kito Gallery MSMEs, was the foundation for cultural preservation and economic empowerment. Through the Palembang CINDO (Clean batik inative for Indonesia) initiative, which has used batik dyes from horticultural waste and food residues,2).Residues from gambier extract or gambier, has the lowest percentage, which was 8.20% of the total waste used. On the other hand, the highest percentage was found in